Indeks Desa Zakat Pada Desa Penambangan Kabupaten Sidoarjo 2015–2018 - Mukhammad, Wildhan; Aji, Tony Seno (ZISWAF, 2020)
This study explained the development of zakat-based villages, a method published as a form of response to the less than optimal government programs as well as an alternative in villages development. This study focused on the priority status of the feasibility of a Penambangan Village as an object of research in receiving zakat funds as a form of zakat-based village development. The research method used in this study was a quantitative method, the data used in this study were primary data where the data collection tool used was a questionnaire that has been provided and validated by BAZNAS, and the data processing method used in this study was the Indeks Desa Zakat. The Indeks Desa Zakat (IDZ) is a Process-Oriented-based measuring instrument which not only assesses the appropriateness of an object (village, community) in receiving zakat funds but also evaluates programs that are already running or that have been carried out. IDZ was a derivative of Zakat Community Development (ZCD), that acts as an empowerment program for productive zakat funds. There were nineteen samples used in this study, consist of all RT (rukun tetangga) in Penambangan Village. The results of this study indicated that Penambangan Village has a good condition so that it is less referred to be assisted through zakat fund.